Pembelajaran Matematika Berbantuan Software Algebrator untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa - Uba Umbara; Inri Rahmawati (Universitas Hamzanwadi, 2018)
The students' mathematical understanding is important to master. Mathematical understanding is also one of the goals of each material presented by the teacher, because the teacher is a guide to achieve the expected concept. Although already has the ability of a mathematical language is needed, but the belief in the field of this ability is still not fully reinforced by students. This study aims to examine the comparison of the ability to understand mathematically students who apply Algebrator software-assisted learning and students who use regular learning and examine differences in the ability to improve students' mathematical understanding of Algebrator-assisted learning software and students using ordinary learning. The research method used in this research is quasi experiment with non-equivalent control group design (unequal control group design). The result of hypothesis test shows that there is a difference in the ability of understanding of mathematics significantly between the students with high, medium and low ability level. This is possible by the improvement of mathematical ability of students triggered by Algebrator software-assisted mathematics learning which in the implementation of learning always pay attention to students centered